2017
DOI: 10.20471/acc.2017.56.02.05
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Optic Nerve Head Morphology in Patients with Primary Open Angle Glaucoma and Non-Arteritic Anterior Ischemic Optic Neuropathy

Abstract: SUMMARY -Th e aim of this study was to assess damage to retinal ganglion cells (RGC) and morphology of the optic nerve head (ONH) in patients with primary open angle glaucoma (POAG) and non-arteritic anterior ischemic optic neuropathy (NAION). Th e study included three groups of patients, as follows: 40 eyes with POAG, 40 eyes with NAION and 40 eyes with refraction anomaly. All patients underwent standard automated perimetry and analysis of ONH topography by using confocal scanning laser ophthalmoscopy (CSLO)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 27 publications
0
13
1
1
Order By: Relevance
“…Recently, confocal scanning laser ophthalmoscopy has become popular because it allows quantitative analysis of the optic nerve head. This scanning method is frequently used for diagnosing and monitoring glaucoma, optic nerve pathologies, and various retinal diseases [18][19][20]. In the present study, the cup-to-disc ratio was higher in the patients with neovascular and nonneovascular AMD than in the control subjects, which was in contrast to that reported by the EDDC study group.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Recently, confocal scanning laser ophthalmoscopy has become popular because it allows quantitative analysis of the optic nerve head. This scanning method is frequently used for diagnosing and monitoring glaucoma, optic nerve pathologies, and various retinal diseases [18][19][20]. In the present study, the cup-to-disc ratio was higher in the patients with neovascular and nonneovascular AMD than in the control subjects, which was in contrast to that reported by the EDDC study group.…”
Section: Discussioncontrasting
confidence: 89%
“…Recently, confocal scanning laser ophthalmoscopy has become popular because it allows quantitative analysis of the optic nerve head. This scanning method is frequently used for diagnosing and monitoring glaucoma, optic nerve pathologies, and various retinal diseases [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Optic Nerve Head Clear differences in ONH parameters were identified through OCT (and HRT) imaging: glaucomatous eyes had a greater cup area, C/D ratio, cup volume, and cup depth and a lower (vertical) rim volume and rim area compared to AION eyes [9,11,12,14,17,21,40]. Danesh-Meyer et al [17] presented a hypothesis that both OAG and AION result in damage to the prelaminar and laminar zone of the ONH but at a different degree of severity and with a different preference for damaging specific structures.…”
Section: Discussionmentioning
confidence: 99%
“…Two of them used VF perimetry, HRT, color fundus photography, and GDx [12,14], and another study used CDI to examine hemodynamic parameters [50]. Two studies examined morphological ONH differences by HRT II and concluded that NAION eyes showed significantly lower cup area, C/D ratio, and mean cup depth, whereas NRR and rim area were significantly greater compared to OAG eyes [12,14]. A larger number of sectors affected in the upper part of ONH in NAION than in POAG eyes were also identified.…”
Section: Other Examination Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation